Looking in From the Outside: Perspectives of Caring for an Individual Diagnosed with Agenesis of the Corpus Callosum - A. Delello, Julie; McWhorter, Rochell R. (IJRDO - Journal of Social Science and Humanities Research, 2017)
Agenesis of the corpus callosum (AgCC) is a rare condition in which the neural connection between the left and right hemispheres of the brain is missing. This descriptive phenomenological study included the voices of 82 individuals, spanning three countries, who were identified as family members and caregivers of individuals diagnosed with AgCC, and three adults diagnosed with AgCC living independently. Analysis of the data revealed there was a lack of information about the disorder to support families and health professionals. Results of the study provide insight into the financial struggles, relationship issues, and the hopes for the future through the lived experiences of the participants. There is an undeniable impact upon families of individuals born with disabilities. As the number of individuals with AgCC continues to escalate due to improved medical techniques, proactive problem-solving for children and adults with AgCC must be considered.